Self-Sustaining Solutions for Streams, Wetlands, and Watersheds, 12-15, September 2004
DOI: 10.13031/2013.17368
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Macrophyte Species on Subsurface Flow Wetland Performance in Cold Climate

Abstract: Horizontal subsurface flow constructed wetlands (HSSCW) allows organic matter and nitrogen removal of fish farm effluent prior to streams discharge. The effect of macrophyte species on HSSCW efficiency was tested in ten units in a greenhouse experiment, in summer and winter. Planted units were at least 5% more efficient in pollutant removal than unplanted units in summer and at least 10% in winter. The increase in removal efficiency for planted units was small, mainly because of the low loading conditions of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
1
2
1
Order By: Relevance
“…aboveground biomass was positively related to water depth in a Great Lakes wetland. Our results also differ from previous studies that did not find a difference in belowground biomass between cattail and P. australis-invaded communities (Ouellet-Plamondon et al, 2004;Rothman and Bouchard, 2007). A major difference between our study and others examining below ground biomass in P. australis-invaded marhes (e.g., Farnsworth and Meyerson, 2003;Rothman and Bouchard, 2007) is that we used the in-growth core technique because our interest was in annual standing stocks, whereas other field studies typically used traditional soil core methods to measure total belowground standing crop biomass.…”
Section: Outcome Of Invasion Depends On Nutrient Environment and Water Depthcontrasting
confidence: 99%
See 3 more Smart Citations
“…aboveground biomass was positively related to water depth in a Great Lakes wetland. Our results also differ from previous studies that did not find a difference in belowground biomass between cattail and P. australis-invaded communities (Ouellet-Plamondon et al, 2004;Rothman and Bouchard, 2007). A major difference between our study and others examining below ground biomass in P. australis-invaded marhes (e.g., Farnsworth and Meyerson, 2003;Rothman and Bouchard, 2007) is that we used the in-growth core technique because our interest was in annual standing stocks, whereas other field studies typically used traditional soil core methods to measure total belowground standing crop biomass.…”
Section: Outcome Of Invasion Depends On Nutrient Environment and Water Depthcontrasting
confidence: 99%
“…and P. australis measured in our study, this inferior nutrient assimilation is likely attributable to lower standing crop biomass in meadow marsh. Indeed, the aboveground biomass in meadow marsh reported in our study is similar to that reported in a greenhouse experiment (1,057 ± 12 g/m 2 ; Ouellet-Plamondon et al, 2004), and lies well below the standing crop biomass values for cattail marsh and P. australis-invaded marsh.…”
Section: Outcome Of Invasion Contingent On Community Being Replacedsupporting
confidence: 89%
See 2 more Smart Citations